The best damn firewall book period - Shinder, Thomas W.; Carasik, Anne H. (Rockland, MA : Syngress, 2003)
This book is essential reading for anyone wanting to protect Internet-connected computers from unauthorized access. Coverage includes TCP/IP, setting up firewalls, testing and maintaining firewalls, and much more. All of the major important firewall products are covered including Microsoft Internet Security and Acceleration Server (ISA), ISS BlackICE, Symantec Firewall, Check Point NG, and PIX Firewall. Firewall configuration strategies and techniques are covered in depth. The book answers questions about firewalls, from How do I make Web/HTTP work through my firewall? To What is a DMZ, and why do I want one? And What are some common attacks, and how can I protect my system against them? The Internet's explosive growth over the last decade has forced IT professionals to work even harder to secure the private networks connected to itfrom erecting firewalls that keep out malicious intruders to building virtual private networks (VPNs) that permit protected, fully encrypted communications over the Internet's vulnerable public infrastructure. The Best Damn Firewalls Book Period covers the most popular Firewall products, from Cisco's PIX Firewall to Microsoft's ISA Server to CheckPoint NG, and all the components of an effective firewall set up. Anything needed to protect the perimeter of a network can be found in this book. - This book is all encompassing, covering general Firewall issues and protocols, as well as specific products. - Anyone studying for a security specific certification, such as SANS' GIAC Certified Firewall Analyst (GCFW) will find this book an invaluable resource. - The only book to cover all major firewall products from A to Z: CheckPoint, ISA Server, Symatec, BlackICE, PIX Firewall and Nokia.
Includes index.
Keywords: Firewalls (Computer security); Computer security -- Computer programs; Electronic books